Fate and transformation of iodine species during Mn(VII)/sulfite treatment in iodide‐containing water. (23rd September 2022) - Shao, Binbin; Zhu, Yating; Chen, Jie; Lin, Yimin; Guan, Xiaohong
Abstract: During oxidative treatment of iodide (I − )‐containing waters, I − is easy to be oxidized into hypoiodous acid (HOI) by various oxidants and the further reaction of HOI with organic compounds can lead to the formation of iodinated disinfection by‐products (I‐DBPs). Oxidation of HOI to iodate (IO3 − ) or reduction of HOI to I − has been proposed to reduce the formation of I‐DBPs. Because the reaction of HOI with sulfite proceeds rapidly, this study examined the fate of iodine and the formation of I‐DBPs in Mn(VII)/sulfite process. Results showed that I − was oxidized to HOI but the further formation of IO3 − was suppressed due to the fast reduction of HOI to I − by sulfite. The reactions of HOI with SO3 2− and IO − with SO3 2− are the major pathways with species‐specific second‐order rate constants determined to be 1.12 × 10 5  M −1  s −1 and 9.43 × 10 7  M −1  s −1, respectively. The rapid reaction of HOI with sulfite plays an essential role in minimizing the formation of iodinated products in HOI‐ and phenol‐containing solutions. The toxic risk analysis showed that the toxicity of the generated DBPs from Mn(VII)/sulfite pre‐oxidation followed by chlorination only changed slightly. Practitioner Points: The decay of I − was negligible in Mn(VII)/sulfite process. The rapid reaction of HOI with SO3 2− resulted in the negligible generation of IO3 − . Mn(VII)/sulfite process exerted slight influence on the formation of I‐DBPs. Mn(VII)/sulfite process is promising for the pretreatment of I − ‐containing water. Abstract : During Mn(VII)/sulfite treatment, I − was oxidized to HOI but the further formation of IO3 − and I‐DBPs was suppressed due to the rapid reaction of HOI with sulfite. The remaining I − can lead to the formation of I‐DBPs in post‐chlorination, but the Mn(VII)/sulfite pre‐oxidation exerted slight influence on I‐DBPs formation.